Improving and predicting the mechanical properties of foamed and stretched composite poly(lactic acid) films - S. Hussain; A. R. Dickson (eXPRESS Polymer Letters, 2019)
Foamed poly(lactic acid) films reinforced with micro-crystalline cellulose (MCC), were uniaxially stretched to different ratios. At 10% (weight) loading MCC particles gave an approximately 3.5 times improvement in stiffness over unreinforced foams. X-ray tomography and image analysis showed that most MCC particles had low aspect ratios, were randomly oriented and well distributed. Stretching did not change the orientation of the MCC particles. Increases in stiffness with stretching were due to the alignment of the foam cell walls. Electron microscopy and image analysis showed that the foam cells were elongated and the walls aligned in the stretch direction. There was a good fit between measured stiffness and micro-mechanical modelling based on a variation of the Mori-Tanaka model for reinforcing particles randomly oriented in 3 dimensions.